The Effect of Early Mobilization and Body Positioning on Functional Ability in Patients with Acute Ischemic Stroke - Arif Pristianto; Santri Raminda; Zulfa Nadia (Jurnal Ilmiah Kesehatan, 2022)
There are many physical problems in post-stroke conditions which is decreased functional ability. This study aimed to determine the effect of early mobilization and body positioning on functional ability in acute stroke patients. The study design used a single blinding, randomized, and controlled trial. The sample consisted of 20 acute ischemic stroke patients selected randomly and equal distribution between the group of early mobilization and body positioning (ages 45-70, MMT 2+ and given exercises ranging from 24-48 after the attack) and the control group (age 45-70, MMT 2+ and given passive exercises 24-48 after the attack) for seven days in hospital care. All patients were evaluated with Glasgow Coma Scale, Mini-Mental State Exam, and Barthel Index. Paired t-tests and independent t-tests have been used to evaluate and differentiate between groups. The study results showed the treatment group (early mobilization and body position training) to a level of functional ability p<0.05 (p=0.000) and the mean -65. The control group (passive exercise) to the level of functional ability p<0.05 (p=0.000) and the mean-28. The difference effect between the group (early mobilization and body position training) with the control group (passive exercise) on the level of functional ability p<0.05 (p=0.000) with a mean difference was 36.9. Early mobilization and body position training are other approaches that can improve functional abilities in patients with acute ischemic stroke